Imputación del intraneus y extraneus, identificando la posición de garante en delitos de infracción de deber; con referencia al peculado. - Salguero Abarca, Dylan Alexander (2025)
This research focused on the problem of ambiguity and inconsistency in the attribution of criminal responsibility for individuals involved in functional crimes, with special reference to embezzlement in the Ecuadorian legal system. The study highlights the critical distinction between the intraneus (an active subject qualified by their public function and the special duty inherent to it) and the extraneus (an individual who participates in the crime). A qualitative, descriptive, and explanatory approach was adopted methodologically, based on a rigorous legal and documentary analysis of the relevant regulations (COIP, Constitution, UNCAC), specialized doctrine, and national case law. This approach was complemented by expert opinions obtained from judicial operators. The most important findings showed a continuing interpretative tension in Ecuadorian judicial practice between the theory of control over the act and the theory of breach of duty, which are used to determine precisely the participation and authorship in embezzlement. The study emphasizes the need to unequivocally certify the subjective component of intent on both sides, which is essential but often complicated. This includes the “communicability of intent” from the intraneus to the extraneus, in addition to the actual economic damage to the State or the illicit gain obtained. It is argued that, to combat corruption effectively, a comprehensive approach is necessary that goes beyond mere criminal punishment. This includes training judges in specific areas, strengthening administrative controls, and implementing effective asset recovery procedures. The goal is to increase transparency and public confidence in institutions